(untitled) (Global Business Management Review (GBMR), 2020)
The annual general meeting (AGM) minutes act as an integral part of a good disclosure and transparency in delivering corporate information. Through the content of AGM minutes, shareholders can have an overview of the company’s performance. The paper examines the in- depth context of the AGM minutes of listed companies in Malaysia. Using the content analysis, a self-constructed checklist was developed to measure the quality of AGM minutes of listed companies in Malaysia. A sample of 115 AGM minutes from various sectors listed in Bursa Malaysia for the financial year ended December 31, 2016, was reported. The results indicate that the quality of AGM minutes discloses by listed companies relatively low consistent with the prior literature that sought for more exploration on the AGM. Using SPSS version 24, a descriptive analysis was presented in this paper. The low level of AGM minutes’ disclosure among Malaysian listed companies suggests that these companies merely disclose within the mandatory requirements. The initiative by the Minority Shareholder Watch Group (MSWG) encourages more disclosure cause listed companies to disclosure additional information such as AGM minutes’ content. The result of this study provides meaningful information, especially on the quality of AGM minutes’ disclosure in Malaysian listed companies, which remained largely unexplored. The study provides insight contribution of the quality AGM minutes on the corporate website prior implementation of Companies Act 2016.